Strategi Komunikasi Guru Dalam Proses Belajar Anak Tunanetra Dengan Menerapkan Multimodal Learning Di Sekolah Luar Biasa Negeri A Bandung (Jurnal Ilmu Komunikasi dan Bisnis, 2018)
Communication is a social activity in the learning process. Teachers are required to have their own learning strategies by utilizing other sensory tools except visual sensory. To achieve learning objectives, teacher communicate the learning materials by applying several methods. One of the learning methods that teacher applied in special school for blind students is multi modal learning method. Multimodal learning is a learning activity by combining several methods of learning methods so the message more widely and more easily understood by students with visual impairment. Not only forming the learning method, but teacher that teach in special school for blind students also has its own strategy to sending the learning messages to students with visual impairment in the classroom. The purpose of this research is to see how strategy communication that teacher do in the class to teach the visual impairment students and communication pattern between teacher and students with application multimodal learning method in class. This research uses constructivist paradigm through case study approach. The result of this research shows that The result of the research shows that there are stages of learning strategy which is done by teacher in the class, that is the stage of forming the personal relationship, the stages form the proximity relationship, the stages of choosing the teaching materials, the stages of delivery strategy by applying multi modal learning that is combination of auditory-kinesthetic learning style, kinesthetic visual-visual, the learning stages and the teacher's response to the students. The strategy is communicated by applying a two way communication pattern in the classroom.